Comparison of intracellular pH transients in single ventricular myocytes and isolated ventricular muscle of guinea-pig. - Bountra, C; Powell, T; Vaughan-Jones, R (1990)
1. Intracellular pH was recorded (double-barrelled pH-selective microelectrodes) in single ventricular myocytes and whole papillary muscles isolated from guinea-pig heart. Both preparations were acid-loaded by various manoeuvres (addition and removal of external NH4Cl or CO2) in order that a comparison could be made of the size and speed of intracellular pH changes and hence of the apparent intracellular buffering power (beta). 2. For the same acid-loading procedure, the size of intracellular pH (pHi) changes was about threefold larger in the isolated myocyte than in whole papillary muscle. The rate of initial acid loading as well as the subsequent rate of pHi recovery (caused by acid extrusion from the cell) were also threefold faster in the myocyte. Estimates of apparent intrinsic (non-CO2) buffering power, based upon the size of pHi changes during acid loading, were 15-20 mmol l-1 for the myocyte and about 70 mmol l-1 for whole muscle. This latter value is similar to previous estimates of beta in heart. 3. When acid extrusion was reduced by applying a high dose of amiloride (1 mmol l-1), then the size of the pHi change during acid loading increased greatly in papillary muscle but changed much less in the myocyte; beta now appeared to be about 30 mmol l-1 in whole muscle but remained essentially unchanged in the myocyte. 4. We conclude that previous values for beta in cardiac muscle have been greatly overestimated because of the presence of sarcolemmal acid extrusion. Paradoxically, this error in estimating beta is far less evident in the isolated myocyte. We suggest that this is because a much more rapid acid loading is achievable in the myocyte so that acid loading will be blunted less by acid extrusion than in whole muscle. We present a simple mathematical model that demonstrates this phenomenon. We conclude that beta in ventricular muscle is likely to resemble that measured in the isolated myocyte, i.e. 15-20 mmol l-1. 5. Slow acid loading in whole ventricular muscle will also affect the kinetics of pHi changes. The model indicates that the rate of pHi recovery from an acid load in papillary muscle does not reflect the pHi dependence of acid extrusion. Instead, it is heavily influenced by the slow rate of acid loading. This emphasises that great care should be taken when interpreting the kinetics of pHi changes in multicellular ventricular preparations.